Western Motifs and Forms in Post-Byzantine Painting of Muscovy; Preliminary Thoughts - Preobrazhenskij, Aleksandr S. (Actual Problems of Theory and History of Art, 2016)
The paper deals with the important issue of West European influence on Russian painting of the late 15th–16th centuries. While Western components in Russian architecture of this period, as well as in the 17th century architecture and painting have been explored quite extensively, there are only few case studies of European motifs used by Russian painters before the Time of Troubles (1605–1613). Our paper can’t cover all significant cases and types of adaptation of Western forms in this period. It aims to show chronological frames of the process which started circa 1530s; the ways of interpretation of adopted motifs that sometimes would affect only iconography of compositions, but rather often transformed their style of Byzantine origin, and the stylistic nature of forms in question. The author argues that Russian painters mainly used not Italian Renaissance but rather archaic late Gothic or Northern Renaissance models, as well as Post-Byzantine Greek works which, having been considered as Orthodox, included Western (Gothic or Proto-Renaissance) elements of iconography and style. It seems that in the 16th century Russia, Western as well as revived Palaeologan forms were used as the instruments of creating new emotional style appropriate for peculiar features of religious mind of the period.Alongside compositions including Western elements, there are some other phenomena in Russian 16th century art that could be defined as a result of European influences. Among them one should point at the new concept of church interior created by Italian architects at the service of Moscow sovereigns. These unified spaces became a serious obstacle for making wall-paintings traditional for Byzantine and Russian churches of the previous period. Still, as time passed, some of these churches were decorated with murals, whose structure appeared to be influenced by “Renaissance” architecture of such buildings. The aspects of the Western impact on Russian 16th century painting are yet to be explored. However, in general, such contacts can be considered as one of the most significant features of Late Medieval Muscovite culture. They reveal its specific “imperial” nature as well as its inner kinship with Post-Byzantine Greek culture and the South Slavic world which developed in a dialogue with Renaissance Europe since the 15 th century.
Keywords: Medieval Russian art; Byzantine art; Western European art; Gothic; Renaissance; Post-Byzantine period; icon painting; wall painting; illuminated manuscripts